2020
DOI: 10.32383/appdr/112429
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Different Extracts From Allium Ursinum Leaves

Abstract: Allium ursinum L. (A. ursinum, family Amaryllidaceae), better known under the name of wild garlic, ramson or bearís garlic is a perennial herbaceous plant. It naturally grows in fens and marshes of Europe and Asia (1-3). Increasingly, popular in European kitchen A. ursinum can be used as a salad, spice or vegetable since all parts of the plant are edible. Throughout history leaves, bulbs and the aerial part of this plant species have been used in traditional medicine as therapeutic and prophylactic agents (4-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…These constituents that were present in the unpolar extract could determine the total activity of the samples. Similarly, in the studies of Tomovic and co-investigators [38], the chloroform extract from Allium ursinum chives exhibited a significantly stronger antimicrobial action than methanol or water extracts. Chloroform extract from the chives was the most active against B. subtilis ATCC 6633 (MIC = 0.313 mg/mL), for B. cereus (MIC = 2.5 mg/mL) and S. aureus (MIC = 2.5 mg/mL).…”
Section: The Determination Of the Antimicrobial Activity Of The Extractsmentioning
confidence: 69%
“…These constituents that were present in the unpolar extract could determine the total activity of the samples. Similarly, in the studies of Tomovic and co-investigators [38], the chloroform extract from Allium ursinum chives exhibited a significantly stronger antimicrobial action than methanol or water extracts. Chloroform extract from the chives was the most active against B. subtilis ATCC 6633 (MIC = 0.313 mg/mL), for B. cereus (MIC = 2.5 mg/mL) and S. aureus (MIC = 2.5 mg/mL).…”
Section: The Determination Of the Antimicrobial Activity Of The Extractsmentioning
confidence: 69%
“…From some different isolation methods of several studies, it was reported that A. ursinum extract contains p -coumaric acid, ferulic acid, kaempferol, kaempferol-3- O -glycoside, ursolic acid, quercetin, phenol compound [ 7 , 10 , 71 ], allicin [ 21 ], malondialdehyde (MDA), carotenoids [ 27 , 50 , 68 ], kaempferol-3,7-di- O -β-D-glucopyranoside, kaempferol-(acetylhexoside)-hexoside, acetyl-kaempferol-deoxyhexose [ 71 ], propylene sulfide, dimethyldisulfide, dimethylthiophene, ( E )-methyl-2-propyl disulfide, ( Z )-methyl-2-propenyl disulfide, dimethyl trisulfide, di-2-propenyl disulfide, 2-vinyl-1,3-dithiane, ( E )-propenyl propyl disulfide, ( Z )-propenyl propyl disulfide, methyl-2-propenyl trisulfide, 3,4-dihydro-3-vinyl-1,2-dithiine, 2-vinyl-4H-1,3-dithiine, dimethyl tetrasulfide, ( E )-di-2-propenyl trisulfide, ( Z )-di-2-propenyl trisulfide, di-2-propyl trisulfide, di-2-propenyl tetrasulfide [ 72 ], inulin, nystose, and I-ketose [ 68 ] ( Figure 5 ).…”
Section: Isolation Methods and Compound Content Of Allium Species Leavesmentioning
confidence: 99%
“…From some different isolation methods of several studies, it was reported that A. ursinum extract contains p-coumaric acid, ferulic acid, kaempferol, kaempferol-3-O-glycoside, ursolic acid, quercetin, phenol compound [7,10,71], allicin [21], malondialdehyde (MDA), carotenoids [27,50,68], kaempferol-3,7-di-O-β-D-glucopyranoside, kaempferol-(acetylhexoside)-hexoside, acetylkaempferol-deoxyhexose [71], propylene sulfide, dimethyldisulfide, dimethylthiophene, [72], inulin, nystose, and I-ketose [68] (Figure 5).…”
Section: Allium Ursinummentioning
confidence: 99%
See 2 more Smart Citations